2015
DOI: 10.1080/10298436.2015.1019496
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of cement-stabilised mixes with steel slag

Abstract: In this study, we evaluated the elastic and mechanical properties of a new type of cement-stabilised material made with steel slag, varying the content of cement and steel slag. To study the elastic properties of these mixes, we measured their density, compressive strength and ultrasound pulse velocity at curing ages of 7, 28 and 90 days. The aggregate type and curing age greatly affected the elastic properties and varied much depending on the cement content. The Poisson's ratio chosen in analyses had little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Given this commonality, established relationships for conventional concrete in relation to elastic modulus (static and dynamic) were then compiled as shown in Figure 5 b. This included using published relationships between elastic modulus and both UPV [ 38 , 49 ] and compressive strength [ 50 , 51 ]. With measured values from this study used as inputs into related prediction equations, comparable relationships existed for both approaches, with resulting values of static ( E s ) and dynamic ( E d ) elastic modulus ranging from 12–26 and 23–40 GPa respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Given this commonality, established relationships for conventional concrete in relation to elastic modulus (static and dynamic) were then compiled as shown in Figure 5 b. This included using published relationships between elastic modulus and both UPV [ 38 , 49 ] and compressive strength [ 50 , 51 ]. With measured values from this study used as inputs into related prediction equations, comparable relationships existed for both approaches, with resulting values of static ( E s ) and dynamic ( E d ) elastic modulus ranging from 12–26 and 23–40 GPa respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Authors concluded that, by using the coarse steel slag, the new material achieves smaller dry shrinkage strain compared to the cement stabilized macadam. Barišić et al [14,15] discovered that steel slag contributes to an increase in compressive strength and dynamic modulus of elasticity in mixtures where gravel is partly replaced with steel slag. Furthermore, a steel slag mixture has a higher compressive strength and a higher dynamic modulus of elasticity under freezing or thawing conditions than stabilized gravel, which is the result of the rough surface of steel slag, contributing to stronger bonding in the interfacial transition zone (ITZ).…”
Section: Steel Slagmentioning
confidence: 99%
“…Liu et al [12] Li et al [13] Barišić et al [14,15] Passeto i Baldo [16] Inhibitive effect on drying shrinkage Higher compressive strength and dynamic moduli of elasticity Better resistance to freeze -thaw cycles Stronger bonds in ITZ Up to 50 % replacement of natural aggregates Detrimental effect on rigidity Toxicological by-products…”
Section: Steel Slagmentioning
confidence: 99%
“…In a recent study [23], the values of compressive strength, tensile strength, and dynamic modulus of elasticity (measured by ultrasound pulse velocity method) for cement stabilized gravel with 4% cement content were measured and obtained as 3.31 MPa, 0.61 MPa and 13.89 GPa, respectively. Thus, with respect to stress and strain analyses, the variations in the values of dynamic modulus of elasticity included 15 GPa, 10 GPa, and 5 GPa to define crack propagation on pavement stress/strain state.…”
Section: Analyses Of Pavement Structure By Analytical Methods (Bisar mentioning
confidence: 99%